Lateral optimization of aircraft tracks in Reykjavik air traffic control area - Einar Ingvi Andrésson 1985- (2012)
The requirement of minimizing fuel oil burn and greenhouse gas emissions in aviation is an ever increasing factor in air traffic management. The approach used in this project is to minimize fuel burn and emissions by optimizing flight tracks with respect to wind. This is based on the assumption that by minimizing the flight time between two points, the amount of fuel is also minimized. The optimization is done with the Dijkstra search algorithm, which is used to calculate the shortest path in terms of time for aircrafts in cruise phase. A geographical grid is constructed using flight plans from Icelandair, with the initial flight plan as a reference point to calculate the shortest path through. The starting coordinates and last known coordinates for cruise phase during the flights were used as the starting and end points for the algorithm. Two flights originating in Iceland were examined in detail and both showed reduction in the time spent in cruise phase from their respective flight plans. These improvements were also used to estimate the fuel saved per kilograms. The reduction in fuel burn was subsequently used to estimate the reduction of CO$_2$ emissions during the cruise phase. The results show that using wind optimization to reduce cruise time with a shortest-path search algorithm can likely offer opportunities for improved fuel efficiency and merits further research. Further research of this method would be extended to airlines that transit through the Reykjavik control area in cruise phase without landing or take-off from Keflavik, giving a better picture of traffic within the Reykjavik control area. Kröfurnar um að minnka eldsneytisbrennslu og útblástur gróðurhúslofttegunda í flugumferð er sífellt að öðlast meira vægi í flugumstjórn. Aðferðin til lágmarka eldsneytisbrennslu og útblástur í þessu verkefni er með bestun á flugferlum með tilliti til vinda, bæði vindhraða og vindáttar. Bestunin var framkvæmd með Dijkstra leitaralgríminn, sem finnur þá flugleið fyrir flugvélar í flughæð sem lágmarkar ...